Extent of E-Learning Contribution in Quality Assurance of Higher Education "Case Study of Accounting Learning in the Jordanian Universities - Walid Zakaria Siam (University of Science and Technology, Yemen, 2013)
Abstract This study aimed at highlighting the extent of e-learning contribution in quality assurance of higher education via a case study of accounting learning in the Jordanian Universities, and measuring the extent of perception of faculty members at the accounting departments in the Jordanian universities. In addition, this study aimed at determining the extent of using e-learning and the benefits achieved by this use in the expansion of university learning and the reinforcement of human development. To achieve the study objectives, a questionnaire was developed and distributed by hand on a sample of faculty members at the accounting departments in the Jordanian universities, where (52) questionnaires were adopted among the sixty distributed questionnaires. Via statistically analyzing the questionnaires answers it has been shown that the faculty members at the accounting departments are aware of the importance of e-learning in the university accounting teaching, however, the actual use of e-learning in the university accounting teaching is still limited because of the existence of obstacles (determinants) related the faculty members, students, and available technical and material potentials. Keywords: E-Learning, Quality Assurance of Higher Education.